Challenges of innovative architecture: education and practice - Augustinaitė, Dalia (Journal of Architecture and Urbanism, 2018)
The article analyzes the concept of innovative architecture, which is significant in developing the anthropogenic environment, explains the structural and systemic components that form it and the relations between them. The research focuses on the Lithuanian culture and the educational system of its architecture schools as a means contributing to the development of innovative thinking skills. On this basis, it explains what advantages and disadvantages of the education system in the country reflect the present practice of innovative architecture. At the end of the article, considering the present situation, suggestions are made on how to improve the quality of the relationship between education and practice.